Risk of Cardiovascular Disease Associated with HCV and HBV Coinfection among Antiretroviral-Treated HIV-Infected Individuals. Issue 3 (April 2014) - Gillis, Jennifer; Smieja, Marek; Cescon, Angela; Rourke, Sean B; Burchell, Ann N; Cooper, Curtis; Raboud, Janet M; ,
Background: The increased risk for cardiovascular disease (CVD) in HIV is well established. Despite high prevalence of viral hepatitis coinfection with HIV, there are few studies on the risk of CVD amongst antiretroviral therapy (ART)-treated coinfected patients. Methods: Ontario HIV Treatment Network Cohort Study participants who initiated ART without prior CVD events were analysed. HBV and HCV coinfection were identified by serology and RNA test results. CVD was defined as any of: coronary artery disease including atherosclerosis, chronic ischaemic heart disease and arteriosclerotic vascular disease; myocardial infarction; congestive heart failure; cerebrovascular accident or stroke; coronary bypass; angioplasty; and sudden cardiac death. The impact of HBV and HCV coinfection on time to CVD was assessed using multivariable competing risk models accounting for left truncation between ART initiation and study enrolment. Results: A total of 3, 416 HIV-monoinfected, 432 HIV-HBV- and 736 HIV–HCV-coinfected individuals were followed for a median (IQR) of 2.32 years (1.36–8.02). Over the study period, 167 CVD events and 613 deaths were documented. After adjustment for age, gender, race, year initiating ART, weight and smoking status, HBV was not associated with time to CVD onset (aHR=1.05, 95% CI [0.63, 1.74]; P =0.86). There was an elevated risk of CVD for HCV-coinfected individuals, which approached statistical significance (aHR=1.44, 95% CI [0.97, 2.13]; P =0.07). Conclusions: Our results are consistent with a moderate increase of CVD among individuals with HIV–HCV coinfection relative to those with HIV infection alone, lending support to consideration of initiation of HCV antiviral treatment.